Development of Jakarta-Bandung Fast Rail Infrastructure - Fadilah, Restu Fauziah; Abdul Qodir Jaelani (GoResearch - Research & Publishing House, 2023)
The government should pay more attention to the infrastructure in its country so that it is not left behind by other countries. To make this happen, development in the infrastructure sector is needed. One of the developments carried out by the Indonesian government, Joko Widodo, is the development of infrastructure in the mass transportation sector, namely the Fast Train. This project is President Joko Widodo's priority because it is more economical, safe, comfortable and more efficient in travel time. Even though there was a delay in completion plus several risks that had to be borne by related parties, this project was finally successfully completed in October 2023 and the benefits have been felt by more than 718 thousand passengers since its inauguration until December 8 2023. This research uses qualitative research methods with descriptive approach. The data collection technique used in this research is through literature review. The aim of this research is to find out how fast train infrastructure is being developed and what the obstacles are in its implementation.